2022
DOI: 10.4081/ija.2022.2129
|View full text |Cite
|
Sign up to set email alerts
|

Climate change risk perception and adaptation to climate smart agriculture are required to increase wheat production for food security

Abstract: Climate change poses a serious risk to wheat farmers in many regions of the world. The present study was conducted in the Sialkot District, Punjab, Pakistan, to investigate climate change trends during the past thirty years and to determine farmers’ knowledge and perceptions about climate change. The study also addresses the impacts of climate change on wheat production, current adaptation strategies, and limitations in adaptations to climate-smart agriculture (CSA) through a questionnaire-based survey. The hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“…Therefore, it was suggested that CSA practices should be adopted globally. [17] Ehsan, Nusrat et al suggested that farmers should be trained and institutional services in the form of consultation should be provided which specifically focuses on climate-centric farming resulting in climate-smart agricultural practices for better food security [18]. To enhance the effectiveness of various Climate-Smart Agriculture Programs (CSAPs), the research suggests the need for efficient coordination among diverse stakeholders at the local level.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, it was suggested that CSA practices should be adopted globally. [17] Ehsan, Nusrat et al suggested that farmers should be trained and institutional services in the form of consultation should be provided which specifically focuses on climate-centric farming resulting in climate-smart agricultural practices for better food security [18]. To enhance the effectiveness of various Climate-Smart Agriculture Programs (CSAPs), the research suggests the need for efficient coordination among diverse stakeholders at the local level.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Variability in precipitations is occurring at both intra-annual and inter-annual levels. This variability has a strong impact on the agricultural sector (Todorović et al, 2021;Ehsan et al, 2022), especially for herbaceous crops with a spring-summer cycle that are cultivated in areas where rainfall used to almost fully meet the crop's evapotranspiration demand. In this context, irrigation is now an indispensable agronomic technique to achieve sustainable yield levels (Tran et al, 2020).…”
Section: Introductionmentioning
confidence: 99%